Pasticcio, Arrangement, or Adaptation? Georg Philipp Telemann's Pasticcio Judith Based on Fortunato Chelleri's dramma per musica Innocenza difesa - zur Nieden Gesa (Musicology Today, 2021)
In musicological research on the eighteenth-century operatic pasticcio it has often been discussed how pasticci can be distinguished from dramme per musica. The article examines the evolution of Fortunato Chelleri's opera Innocenza difesa in the course of its adaption for several performance venues (Florence 1720, Venice 1722, Kassel 1725, Wolfenbüttel/Brunswich 1731), as well as pasticcio projects based on Chelleri's score (Hamburg 1732). By analysing the surviving libretti, scores, and sheet music related to Chelleri's opera, it can be shown that Chelleri as well as the arranger of the Hamburg pasticcio-production, Georg Philipp Telemann, paid attention to the overarching dramaturgical principles as well as to new forms of music publishing in large metropolises such as London. Telemann not only chose some arias by George Frederic Handel from among the most celebrated numbers in the opera Lotharius (composed by Handel, printed by John Walsh in London, 1730), but he also fostered Chelleri's focus on Judith as a main character. Within these musical-dramaturgical perspectives, based on very loose networks of connections between librettists, composers, singers, and probably stage designers, requests for specific arias from individual singers could also be accommodated.